Indigenous Data Sovereignty Toward an agenda - Kukutai, Tahu; Taylor, John (ANU Press, 2016)
"As the global 'data revolution' accelerates, how can the data rights and interests of indigenous peoples be secured? Premised on the United Nations Declaration on the Rights of Indigenous Peoples, this book argues that indigenous peoples have inherent and inalienable rights relating to the collection, ownership and application of data about them, and about their lifeways and territories. As the first book to focus on indigenous data sovereignty, it asks: what does data sovereignty mean for indigenous peoples, and how is it being used in their pursuit of self-determination? The varied group of mostly indigenous contributors theorise and conceptualise this fast-emerging field and present case studies that illustrate the challenges and opportunities involved. These range from indigenous communities grappling with issues of identity, governance and development, to national governments and NGOs seeking to formulate a response to indigenous demands for data ownership. While the book is focused on the CANZUS states of Canada, Australia, Aotearoa/New Zealand and the United States, much of the content and discussion will be of interest and practical value to a broader global audience. 'A debate-shaping book ... it speaks to a fast-emerging field; it has a lot of important things to say; and the timing is right.' - Stephen Cornell, Professor of Sociology and Faculty Chair of the Native Nations Institute, University of Arizona. 'The effort ... in this book to theorise and conceptualise data sovereignty and its links to the realisation of the rights of indigenous peoples is pioneering and laudable.' - Victoria Tauli-Corpuz, UN Special Rapporteur on the Rights of Indigenous Peoples, Baguio City, Philippines "